2017
DOI: 10.1111/jzo.12516
|View full text |Cite
|
Sign up to set email alerts
|

Tail regeneration in the Paleozoic tetrapod Microbrachis pelikani and comparison with extant salamanders and squamates

Abstract: Among extant tetrapods, salamanders are the only group capable of full limb and tail regeneration, the latter including the re-establishment of a fully functional tail with the axial skeleton and associated musculature. Tail regeneration is associated with autotomy (self-amputation) in some salamander taxa but is also possible in salamander taxa that lack tail autotomy. Modern squamates also frequently show tail autotomy as a defense or decoy mechanisms against predation, but contrary with salamanders, the tai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 54 publications
(114 reference statements)
0
13
0
Order By: Relevance
“…We refer to regeneration, bone healing, and remodeling as being cell-mediated , because they involve the resorption of bone by osteoclasts and deposition of bone by osteoblasts, whereas biophysical annealing lacks obvious cellular control. All three cell-mediated bone repair processes, but not biophysical annealing, have been discovered in fossils (Capasso et al 1996; Tanke and Currie 1998; Anné et al 2014; Fröbisch et al 2014, 2015; Stilson et al 2016; Pardo-Pérez et al 2018; van der Vos et al 2018). Paleopathologies can provide insight into the evolution of bone repair, because paleopathologies are direct evidence of bone's response to insult.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We refer to regeneration, bone healing, and remodeling as being cell-mediated , because they involve the resorption of bone by osteoclasts and deposition of bone by osteoblasts, whereas biophysical annealing lacks obvious cellular control. All three cell-mediated bone repair processes, but not biophysical annealing, have been discovered in fossils (Capasso et al 1996; Tanke and Currie 1998; Anné et al 2014; Fröbisch et al 2014, 2015; Stilson et al 2016; Pardo-Pérez et al 2018; van der Vos et al 2018). Paleopathologies can provide insight into the evolution of bone repair, because paleopathologies are direct evidence of bone's response to insult.…”
Section: Introductionmentioning
confidence: 99%
“…Fröbisch et al (2014) described limb regeneration in the fossil record in the 300-million-year-old temnospondyl amphibian Micromelerpeton . Tail regeneration in the microsaurs Hyloplesion and Microbrachis resembles that of extant salamanders, and these early tetrapods may also have been able to regenerate limbs (Fröbisch et al 2015; van der Vos et al 2018). Nogueira et al (2016) reported that gene expression is similar in extant salamander limb and lungfish fin regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that also these peculiar fish were capable of broad organ regeneration, including in the fins, as this process is still present in larval and adults of extant dipnoi (Conant, 1970(Conant, , 1972Darnet et al, 2019;Nogueira et al, 2016). Some information, including those derived from the fossil record, indicate that also ancient amphibians went through larval stages during their life cycles, stages needed to transit toward a terrestrial life (Darnet et al, 2019;Fröbisch, Bickelmann, Olori, & Witzmann, 2015;Frobisch, Bickelmann, & Witzmann, 2014;van der Vos, Witzmann, & Frobish, 2017). Aquatic amphibians (urodeles) retained the large genomes present in their ancestor sarcopterigians (Figure 2c), also present in extant lungfishes (Conant, 1970(Conant, , 1972Nogueira et al, 2016, Darnet et al, 2019.…”
Section: Vertebrates Regeneration Depends On Genes Used At Specificmentioning
confidence: 99%
“…Van der Voss et al . () show that Microbrachis was capable of salamander‐like full tail regeneration, with articulating vertebrae in the regenerated part of the tail. These results concur with earlier studies on limb regeneration in basal tetrapods (Fröbisch et al ., ) and suggest that the regenerative capacities of modern salamanders may be the ancient state of tetrapods and were later lost in amniote evolution.…”
mentioning
confidence: 99%
“…Palaeopathology, however, not only documents and analyses the history and evolution of disease, but also healing strategies. In this mini‐series, the study of Van der Voss, Witzmann & Fröbisch () concerns bone regeneration in extant salamanders and a Late Carboniferous stem‐amniote, the microsaur Microbrachis . Salamanders are unique among extant tetrapods in their ability to fully regenerate complete body parts, including their limbs and tail.…”
mentioning
confidence: 99%